Inovasi metode pembelajaran pendidikan agama islam di MI untuk meningkatkan motivasi peserta didik - putri, manda reva (Maliki Interdisciplinary Journal, 2025)
Islamic Religious Education plays an important role in shaping the character and morals of students in Madrasah Ibtidaiyah. The main problems faced are the lack of innovation in learning methods that are in accordance with the characteristics of early age students and the low motivation to learn which has an impact on the understanding and practice of Islamic teachings. The approach used in this study is a literature review from various sources related to learning strategies, psychological theories of child development, and empirical studies on the effectiveness of the methods applied. The proposed solutions include the implementation of interactive, creative learning strategies, and based on the characteristics of the physical and psychological development of early age children in MI. The results of the analysis show that the implementation of innovative and contextual methods can increase learning motivation and students' understanding of Islamic Religious Education material as a whole. It is recommended that there be ongoing training for educators and the development of appropriate learning media so that the learning process is more effective and enjoyable. In conclusion, innovation in learning strategies and methods is very important to improve the quality of religious education at the elementary madrasah level.